1998
DOI: 10.1002/(sici)1521-4095(199804)10:6<439::aid-adma439>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Electrolytes for Lithium-Ion Batteries

Abstract: The motivation for lithium battery development and a discussion of ion conducting polymers as separators begin this review, which includes a short history of polymer electrolyte research, a summary of the major parameters that determine lithium ion transport in polymer matrices, and consequences for solid polymer electrolyte development. Two major strategies for the application of ion conducting polymers as separators in lithium batteries are identified: One is the development of highly conductive materials vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
1,031
0
8

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,350 publications
(1,049 citation statements)
references
References 33 publications
10
1,031
0
8
Order By: Relevance
“…Several extensive reviews give a more detailed description of the different types of polymer electrolytes and their development. [125][126][127] Polymer electrolyte fi lms can be produced using various methods. It was reported that electrolyte fi lms could, for example, be prepared by casting from a polymer solution, [ 128 ] evaporation methods, [ 129 ] or in situ plasma polymerization techniques.…”
Section: Polymer Electrolytesmentioning
confidence: 99%
“…Several extensive reviews give a more detailed description of the different types of polymer electrolytes and their development. [125][126][127] Polymer electrolyte fi lms can be produced using various methods. It was reported that electrolyte fi lms could, for example, be prepared by casting from a polymer solution, [ 128 ] evaporation methods, [ 129 ] or in situ plasma polymerization techniques.…”
Section: Polymer Electrolytesmentioning
confidence: 99%
“…Compared to liquid electrolyte, polymer electrolytes have several advantages over liquid electrolytes including the ability to minimize percent leakage of electrolytes and ensure non-flammable reaction products at the surface of electrodes. [22][23][24] They have been widely used in energy conversion and storage devices. [25][26][27][28] Currently, there are only a few stretchable solid electrolytes reported such as graft copolymer poly[(oxyethylene) 9 Very recently, a stretchable H 2 SO 4 -PVA gel electrolyte has been used to prepare stretchable integrated supercapacitor which can sustain 120% strain.…”
Section: Introductionmentioning
confidence: 99%
“…(iii) Improvement of safety, in addition to suppression of lithium dendrites, the quasi-solid-state construction of a polymer electrolyte is more tolerant to mechanical deformation. (iv) Better shape flexibility and manufacturing integrity [10][11][12][13][14][15][16][17]. Meanwhile, to be successfully used in practice, GPE must meet the following basic requirements: (i) ionic conductivity higher than~10 −4 S cm −1 at room temperature, (ii) lithium ion transference number close to unity, (iii) good thermal, chemical and electrochemical stability and (iv) a considerable mechanical strength [10,12,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%